Blunting neoliberalism tripartism and economic reforms in the developing world - Fraile, Lydia, 1960- (Palgrave Macmillan ; ILO, 2009)
"This volume is one of the first books to consider the impact of tripartism across the developing world. It covers 8 case studies from Afrcia, Asia, Eastern Europe and Latin America, focusing on developments since the 1990s. These studies show that tripartism has the effect of reducing the social impact of neo-liberal economics reforms"--Provided by publisher.